1991
DOI: 10.1083/jcb.114.6.1261
|View full text |Cite
|
Sign up to set email alerts
|

Acidic fibroblast growth factor in the developing rat embryo.

Abstract: Abstract. Compared to basic fibroblast growth factor (bFGF), a widely distributed, broad spectrum mitogen and mesoderm inducer, acidic fibroblast growth factor (aFGF) is reported to have an essentially neural distribution and to be undetectable in the early embryo . In the present investigation, we used immunoblotting and immunochemistry to assess the cellular and tissue distributions of aFGF and bFGF in 11-20-d rat embryos.Immunoblotting of crude and heparin-bound embryo extracts revealed faint bands at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 59 publications
(90 reference statements)
4
56
1
1
Order By: Relevance
“…Both FGFl and FGF2 have been found bound to HSPGs either on the cell surface or in the extracellular matrix (Klagsbrun, 1990) and HSPG-bound FGF1 has been shown to be 100x more mitogenic than heparinbound FGF1 (Gordon et al, 1989). FGF1 has been localized extracellularly in vivo in the developing heart (Engelmann et al, 1993), tooth (Cam et al, 1992), lungs, digestive system, CNS and eye (Fu et al, 1991) where it is thought to act both as a paracrine growth factor as well as stimulating capillary and neural invasion. Weiner and Swain (1989) have shown that neonatal cardiac myocytes deposit FGF1 into their extracellular matrix and FGFR1 transcipts have been localized on developing cardiomyocytes (Engelman et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Both FGFl and FGF2 have been found bound to HSPGs either on the cell surface or in the extracellular matrix (Klagsbrun, 1990) and HSPG-bound FGF1 has been shown to be 100x more mitogenic than heparinbound FGF1 (Gordon et al, 1989). FGF1 has been localized extracellularly in vivo in the developing heart (Engelmann et al, 1993), tooth (Cam et al, 1992), lungs, digestive system, CNS and eye (Fu et al, 1991) where it is thought to act both as a paracrine growth factor as well as stimulating capillary and neural invasion. Weiner and Swain (1989) have shown that neonatal cardiac myocytes deposit FGF1 into their extracellular matrix and FGFR1 transcipts have been localized on developing cardiomyocytes (Engelman et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Synergistic Angiogenesis. Leptin has been found to be coexpressed with other angiogenic factors (including FGF-2 and VEGF) in adipose, placental, and fetal tissues, suggesting that leptin might modulate the angiogenic activity of these factors (3,7,11). To test this possibility, low doses of leptin and FGF-2 or VEGF were coimplanted into mouse corneas.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Fu et al (1991) also reported high and low molecular weight forms of FGF in SD rat embryos. In addition, they detected "faint staining in some nuclei" by immunohistochemistry, but did not state in which specific tissues this occurred or at what stages.…”
Section: Fgf Associated With Plasma Membranes and Nucleimentioning
confidence: 97%
“…11-16, NIH 3T3 cells. Fu et al (1991) suggested that extracellular pools of acidic FGF they immunostained in the central nervous system of embryonic rats could stimulate capillary invasion. In the present study, the demonstration of extracellular dense foci of FGF was a relatively infrequent finding.…”
Section: Immunolocalization Of Fgf Within Gonadotropes and Its Releasmentioning
confidence: 99%